TC4 titanium alloy impact brake and additive manufacturing method thereof

CN122644607APending Publication Date: 2026-08-28ADVANCED FOR MATERIALS & EQUIP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611150585.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

[0004]该方案存在以下缺陷:(1)必须依赖专用模具和工装,生产周期长,设计更改后需重新制备模具,柔性低,响应速度慢;(2)受型砂、温度、浇注速度影响大,易产生气孔、微裂纹等铸造缺陷,批次稳定性差,质量控制难度高

Benefits of technology

[0029]Compared with existing technologies, this invention utilizes additive manufacturing technology to achieve integrated molding of the entire structure of the TC4 titanium alloy impact brake, eliminating the need for molds and welding assembly. This fundamentally eliminates the failure risk of separate welding, significantly shortens the production cycle, and improves the flexibility of design iteration. Through a composite scanning strategy combining partitioned scanning and interlayer rotation, forming defects such as spheroidization, porosity, and incomplete fusion are effectively eliminated, reducing internal stress concentration and achieving defect-free, low-internal-stress integrated molding of the complex structure of the brake. Considering the microstructure characteristics of additively manufactured TC4 and the high-impact, high-alternating-load service conditions of the impact brake, water quenching is employed. Solution treatment and aging treatment, along with water quenching, ensure that the high-temperature solution structure is fully preserved to room temperature, achieving an optimal match between material strength and impact toughness, significantly superior to gas cooling methods in existing technologies. A composite strengthening process, employing ultrasonic rolling followed by laser shock, is used. Ultrasonic rolling forms a nanocrystalline layer on the surface, closing surface defects and introducing shallow compressive stress, while laser shock introduces compressive stress at a deeper level, ultimately forming a continuous residual compressive stress layer with a depth of 1.4-1.6 mm, effectively suppressing the initiation and propagation of fatigue cracks. Therefore, the muzzle brake manufactured by this invention can fully meet the service requirements of high chamber pressure and high alternating impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122644607A_ABST
    Figure CN122644607A_ABST
Patent Text Reader

Abstract

The application discloses a TC4 titanium alloy impact type recoil brake and an additive manufacturing method thereof, and belongs to the fields of additive manufacturing and weapon equipment manufacturing. The method comprises the following steps: model construction and forming preparation, additive manufacturing integrated forming, post-processing, heat treatment strengthening, composite strengthening and finishing. The application adopts a scanning strategy of partition scanning combined with interlayer rotation to realize defect-free forming; the optimal matching of strength and impact toughness is realized through sequentially performed solid solution treatment and aging treatment; a continuous residual compressive stress layer is formed through sequentially performed ultrasonic rolling strengthening and laser impact strengthening. The impact energy of the TC4 titanium alloy impact type recoil brake treated by the method is greater than or equal to 25 J / cm2 at-40 DEG C, the tensile strength is greater than or equal to 1000 MPa, the yield strength is greater than or equal to 840 MPa, and the elongation after fracture is greater than or equal to 14%. Therefore, the application realizes the full-structure integrated near-net forming of the recoil brake, and significantly improves the service reliability and service life of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of additive manufacturing and weapon manufacturing technology, specifically to a TC4 titanium alloy impact brake and its additive manufacturing method. Background Technology

[0002] The muzzle brake is a core functional component of artillery or high-precision sniper rifles. Installed at the front of the barrel, it generates a reverse thrust by impacting the multi-stage baffles and side nozzles within the muzzle brake's internal cavity during firing. This significantly reduces recoil, suppresses muzzle ripple and muzzle flash, and improves firing accuracy and continuous firing stability. TC4 (Ti-6Al-4V) titanium alloy is characterized by high specific strength, excellent corrosion resistance, and significant lightweight properties. Using TC4 material to manufacture muzzle brakes can achieve a weight reduction of over 30% compared to traditional steel materials, making it an important means of improving firing performance.

[0003] Currently, the manufacturing methods of TC4 titanium alloy shear brakes can be mainly classified into the following categories: 1. Casting combined with machining preparation scheme. This scheme adopts the route of "casting blank and multi-axis precision machining". For example, Chinese patent CN114000142A discloses a method for strengthening the nozzle wall of a titanium alloy muzzle brake, which uses traditional casting + machining process to form the body, and finally uses laser cladding technology to strengthen the nozzle wall. Another conventional scheme uses integral casting to machine the part, and then performs chrome plating surface treatment.

[0004] The following defects exist in this scheme: (1) It must rely on special molds and tooling, resulting in a long production cycle. After the design is changed, the molds need to be remade, which is not flexible and has a slow response speed. (2) It is greatly affected by molding sand, temperature and pouring speed, which can easily produce casting defects such as porosity and microcracks. The batch stability is poor and the quality control is difficult.

[0005] 2. Additive Manufacturing Preparation Scheme. Among the published additive manufacturing muzzle brake schemes, Chinese patent CN117512589B discloses a method for preparing a titanium alloy gun barrel muzzle brake with a Ta-W coating. This method uses laser 3D printing technology to print the annular body of the titanium alloy muzzle brake, and then forms a Ta-W coating on the inner wall through laser cladding. However, the laser melting deposition (LMD) technology used in this scheme has low forming accuracy, and the annular body still requires extensive machining and coating treatment after forming, making it impossible to achieve near-net-shape integrated forming of complex internal cavity structures.

[0006] Furthermore, while existing additive manufacturing solutions primarily focus on muzzle brake structure forming, a complete technical solution specifically optimized for the high-impact service conditions of impact-type muzzle brakes using SLM (Surface Mount Technology) processes and heat treatment is still lacking. Existing SLM fabrication methods result in parts prone to defects such as spheroidization, porosity, and incomplete fusion, leading to severe internal stress concentration, subsequent machining deformation, and difficulty in meeting the dimensional accuracy requirements of firearm components.

[0007] 3. Heat Treatment Solutions for TC4 Materials. Publicly available heat treatment solutions for additive manufacturing TC4, such as Chinese patent CN112962041A, disclose a method for improving the fracture toughness of additive manufacturing TC4 titanium alloy materials, employing a dual heat treatment method. This solution only applies stress-relief annealing and two-phase heat treatment to general-purpose additive manufacturing TC4 parts, and does not incorporate a solution-aging strengthening system adapted to the SLM-formed microstructure, taking into account the service characteristics of impact brakes.

[0008] In summary, there is currently a lack of a complete manufacturing method that can balance the high strength and high impact toughness of TC4 titanium alloy muzzle brakes, achieve near-net-shape integrated forming of complex internal cavity structures, and adapt to high chamber pressure and high alternating impact service conditions. Summary of the Invention

[0009] To address the aforementioned shortcomings in the prior art, this invention provides a TC4 titanium alloy impact brake and its additive manufacturing method.

[0010] To achieve the above objectives, the present invention provides an additive manufacturing method for a TC4 titanium alloy impact brake, the method comprising the following steps: S100. Construct an integrated 3D model of the TC4 titanium alloy impact brake to be manufactured, and add a support structure to the suspended position of the 3D model. Then, slice the 3D model with the support structure to generate laser scanning paths for each layer.

[0011] In this step, the three-dimensional model includes a connecting structure, an impact chamber, an impact baffle, and side spray holes. The wall thickness of the three-dimensional model needs to be optimized and the sharp corners need to be rounded to eliminate stress concentration areas. The three-dimensional model is placed vertically on the molding substrate with the muzzle connecting end facing down and the muzzle axis perpendicular to the substrate plane. At the same time, the three-dimensional model has a machining allowance of 0.3-0.5mm.

[0012] In this step, the support structure is a grid-like lightweight support, and a 0.1-0.2mm peeling layer is set on the contact surface between the support structure and the three-dimensional model to avoid damage to the brake substrate after the support structure is removed.

[0013] In this step, the slice thickness is preferably 30-60μm, and the laser scanning path adopts a scanning strategy that combines partitioned scanning with interlayer rotation. The partitioned scanning is an island-style partitioned scanning, and the interlayer rotation angle is 67°. This composite scanning strategy can effectively avoid interlayer stress concentration and reduce molding defects.

[0014] S200. According to the laser scanning path generated in step S100, under the protection of inert gas, the pre-selected TC4 titanium alloy powder is melted and deposited layer by layer by laser selective melting method to form a brake blank.

[0015] In this step, the process parameters for laser selective melting are: laser power 300-500W, scanning speed 800-1500mm / s, scanning line spacing 0.08-0.14mm, slice thickness 30-60μm, and substrate preheating temperature 80-120℃.

[0016] In this step, the inert gas is argon, and the oxygen content in the molding cavity is ≤100ppm. After molding is completed, the blank of the ejector is naturally cooled to room temperature along with the substrate in an inert gas atmosphere.

[0017] S300: Separate the brake blank from the substrate and remove the support structure.

[0018] In this step, it is preferable to use wire electrical discharge machining to separate the ejector blank from the substrate. The cutting position is located at the connection between the support structure and the substrate. At the same time, manual and sandblasting methods are used to remove the support structure and forming burrs.

[0019] In this step, after removing the supporting structure, stress-relief annealing is performed. The process parameters for stress-relief annealing are: vacuum degree ≤ 5 × 10⁻⁶. -3 Pa, hold at 800-850℃ for 2-4 hours, then cool in the furnace to below 200℃ before removing from the furnace to completely eliminate residual internal stress generated during the additive manufacturing process.

[0020] S400. The blank of the brake after the support structure is removed is subjected to heat treatment, wherein the heat treatment includes solution treatment and aging treatment performed in sequence.

[0021] In this step, the solution treatment specifically involves placing the shrinkage device blank into a vacuum heat treatment furnace with a vacuum degree ≤ 5 × 10⁻⁶. - 3 Pa, heat to 900-960℃ at a heating rate of 5-10℃ / min, and hold for 1-2 hours; immediately after holding, perform water quenching treatment with a cooling rate ≥50℃ / s to retain the high-temperature solid solution structure to room temperature.

[0022] The aging treatment specifically involves placing the solution-treated shrink tube blank back into a vacuum heat treatment furnace with a vacuum degree ≤ 5 × 10⁻⁶. -3Pa, heat to 500-650℃ at a heating rate of 5-10℃ / min, hold for 3-5 hours, and then cool to room temperature with the furnace before removing from the furnace.

[0023] S500, The heat-treated blank of the brake is subjected to composite strengthening, wherein the composite strengthening includes ultrasonic rolling strengthening and laser shock strengthening performed in sequence.

[0024] This step also includes pretreatment before composite strengthening: the heat-treated ejector blank is polished to Ra≤3.2μm, and then subjected to acetone soaking, anhydrous ethanol ultrasonic cleaning and drying in sequence.

[0025] The process parameters for ultrasonic rolling strengthening are as follows: using a 27.2-28.8kHz high-frequency ultrasonic rolling device, a YG8 cemented carbide spherical roller, an ultrasonic amplitude of 7-10μm, a static preload of 700-900N, a spindle speed of 350-450r / min, an axial feed of 0.05-0.07mm / r, and a single rolling pass; specifically, a dense nanocrystalline layer is formed on the surface of the blank of the shrinkage device at a depth of 50-130μm, and the open pores and unfused gaps on the surface are closed by plastic rheological compaction, and shallow residual compressive stress is introduced into the surface layer at a depth of 0-0.55mm; then, the rolling debris is blown away with compressed air, and the surface of the workpiece is wiped with anhydrous ethanol and air-dried at room temperature.

[0026] The process parameters for laser shock peening are as follows: using a 1061-1067nm pulsed laser, a pulse width of 15-20ns, a single pulse energy of 22-30J, a square spot size of 4mm×4mm, a scanning overlap rate of 35%-45%, and 2-3 shock passes. During the laser shock peening process, a 0.10mm high-purity aluminum foil is used as the absorption layer, and a 1.0-1.5mm thick continuous flowing deionized water film is used as the constraint layer. The laser shock introduces compressive stress in the deep layer, so that the final continuous residual compressive stress layer depth can reach 1.4-1.6mm.

[0027] S600, the composite-strengthened muzzle brake blank is precision machined to obtain the finished TC4 titanium alloy impact muzzle brake.

[0028] In this step, a CNC lathe is used to machine the connecting internal thread, and the thread accuracy meets the 6H grade tolerance requirement; a five-axis machining center is used to finely finish the inner cavity of the brake and the end face of the nozzle, with a dimensional tolerance of ≤±0.05mm.

[0029] Compared with existing technologies, this invention utilizes additive manufacturing technology to achieve integrated molding of the entire structure of the TC4 titanium alloy impact brake, eliminating the need for molds and welding assembly. This fundamentally eliminates the failure risk of separate welding, significantly shortens the production cycle, and improves the flexibility of design iteration. Through a composite scanning strategy combining partitioned scanning and interlayer rotation, forming defects such as spheroidization, porosity, and incomplete fusion are effectively eliminated, reducing internal stress concentration and achieving defect-free, low-internal-stress integrated molding of the complex structure of the brake. Considering the microstructure characteristics of additively manufactured TC4 and the high-impact, high-alternating-load service conditions of the impact brake, water quenching is employed. Solution treatment and aging treatment, along with water quenching, ensure that the high-temperature solution structure is fully preserved to room temperature, achieving an optimal match between material strength and impact toughness, significantly superior to gas cooling methods in existing technologies. A composite strengthening process, employing ultrasonic rolling followed by laser shock, is used. Ultrasonic rolling forms a nanocrystalline layer on the surface, closing surface defects and introducing shallow compressive stress, while laser shock introduces compressive stress at a deeper level, ultimately forming a continuous residual compressive stress layer with a depth of 1.4-1.6 mm, effectively suppressing the initiation and propagation of fatigue cracks. Therefore, the muzzle brake manufactured by this invention can fully meet the service requirements of high chamber pressure and high alternating impact. Attached Figure Description

[0030] Figure 1 This is a flowchart of an additive manufacturing method for a TC4 titanium alloy impact brake according to the present invention.

[0031] Figure 2 This is a schematic diagram of the structure of the multi-chamber titanium alloy shear device of the present invention.

[0032] Figure 3 This is a cross-sectional view showing the placement of the additive manufacturing model of the heel brake of the present invention.

[0033] In the diagram: 1. Impact baffle, 2. Side spray hole, 3. Support structure. Detailed Implementation

[0034] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way.

[0035] Example 1 like Figures 1-3 As shown, this embodiment provides an additive manufacturing method for a TC4 titanium alloy impact brake, and the specific steps are as follows: S100, Model Construction and Preparation A three-dimensional model of the entire structure, including the connecting internal thread, impact chamber, impact baffle 1, and multiple sets of oblique side spray holes 2, was constructed using three-dimensional modeling software. The wall thickness of the three-dimensional model was optimized and the sharp corners were rounded. Then, the three-dimensional model was placed vertically on the molding substrate with the muzzle connecting end facing down and the muzzle axis perpendicular to the substrate plane, leaving a machining allowance of 0.4mm.

[0036] A grid-like lightweight support structure 3 was added to the overhanging structure of the side spray hole 2 and the inner cavity baffle. A 0.15mm peeling layer was set on the contact surface between the support structure 3 and the 3D model. The slice layer thickness was set to 45μm. The scanning strategy adopted was a composite scanning strategy of island partition scanning combined with interlayer rotation of 67°.

[0037] The SLM molding equipment, which uses inert gas protection, fixes the TC4 titanium alloy substrate in the molding cylinder after sandblasting and ultrasonic cleaning with alcohol. The molding cavity is then evacuated to a vacuum degree of ≤10Pa and filled with high-purity argon gas until the oxygen content is ≤100ppm.

[0038] S200, additive manufacturing integrated molding The additive manufacturing process parameters are as follows: laser power 400W, scanning speed 1200mm / s, scanning line spacing 0.11mm, slice layer thickness 45μm, and substrate preheating temperature 100℃. The entire molding process is protected by argon gas with an oxygen content ≤100ppm. After molding is completed, the preform of the ejector is naturally cooled to room temperature along with the substrate in an argon atmosphere.

[0039] S300, Post-processing The blank of the brake is separated from the substrate by wire electrical discharge machining, and the cutting position is located at the connection between the support structure 3 and the substrate. The support structure 3 and burrs are removed by manual and sandblasting methods (100-mesh white corundum sand, 0.3MPa).

[0040] After removing the support structure 3, the blank of the anemulator is placed in a vacuum heat treatment furnace for stress-relief annealing. The stress-relief annealing process parameters are: vacuum degree ≤ 5 × 10⁻⁶. -3 Pa, heat to 825℃, hold for 3 hours, and then cool in the furnace to below 200℃ before being removed from the furnace.

[0041] S400, heat treatment strengthened The post-processed shrinkage device blank is then subjected to heat treatment, specifically including: Solution treatment, specifically: placing the shrinkage mold blank into a vacuum heat treatment furnace, with a vacuum degree ≤ 5 × 10⁻⁶. -3 Pa, heat to 930℃ at 8℃ / min, hold for 1.5h; immediately water quench, cooling rate ≥50℃ / s.

[0042] The aging treatment specifically involves placing the solution-treated shrink tube blank back into a vacuum heat treatment furnace with a vacuum degree ≤ 5 × 10⁻⁶. -3 Pa, heated to 580℃ at 8℃ / min, held at that temperature for 4 hours, and then cooled to room temperature in the furnace before being removed from the furnace.

[0043] S500, Composite Reinforcement The heat-treated shrinkage device blank is pretreated by using a diamond grinding head to remove sintered powder, burrs, and weld protrusions on the surface of the shrinkage device blank until Ra≤3.2μm; then it is soaked in acetone for 10min, ultrasonically cleaned with anhydrous ethanol for 15min, and dried at 80℃.

[0044] The pretreated shrinkage device blank is subjected to ultrasonic rolling strengthening treatment. Specifically, a 28kHz high-frequency ultrasonic rolling device and a YG8 cemented carbide spherical roller are used. The ultrasonic amplitude is 8μm, the static preload is 800N, the spindle speed is 400r / min, the axial feed is 0.06mm / r, and a single pass of precision rolling is performed. Then, the debris is blown away with compressed air, and the blank is wiped with anhydrous ethanol and air-dried at room temperature.

[0045] The ultrasonically rolled and strengthened blank of the shearer is then subjected to laser shock peening, specifically by: applying a 0.10mm high-purity aluminum foil absorption layer and a 1.2mm thick continuous flow deionized water film constraint layer; using a 1064nm pulsed Nd:YAG laser with a pulse width of 18ns, a single pulse energy of 26J, a square spot size of 4mm×4mm, and a scanning overlap rate of 40%, and performing two shock peening passes.

[0046] S600, precision machining CNC lathe machining of internal threads (6H grade tolerance); five-axis machining center for precision finishing of internal cavities and nozzle end faces (tolerance ≤ ±0.05mm).

[0047] Ultrasonic rolling of the inner cavity gas scouring surface: rolling pressure 15MPa, feed rate 0.15mm / r. After the product passes inspection, chemical passivation treatment is performed to form a TiO2 passivation film on the surface.

[0048] Example 2 The difference between this embodiment and Embodiment 1 is that: In S100: the slice layer thickness is set to 30μm.

[0049] In S200, the additive manufacturing process parameters are: laser power 300W, scanning speed 800mm / s, scanning line spacing 0.08mm, slice layer thickness 30μm, and substrate preheating temperature 80℃.

[0050] In S300: the stress-relief annealing temperature is 800℃, and the holding time is 2h.

[0051] In S400: the solution treatment temperature is 900℃, and the holding time is 1h; the aging treatment temperature is 500℃, and the holding time is 3h; the heating rate is 5℃ / min.

[0052] In the S500: the ultrasonic rolling frequency is 28.8kHz, the ultrasonic amplitude is 7μm, the static preload is 700N, the spindle speed is 350r / min, and the axial feed is 0.05mm / r; the pulsed laser wavelength is 1067nm, the laser shock pulse width is 15ns, the single pulse energy is 22J, and the scanning overlap rate is 35%.

[0053] The remaining steps are the same as in Example 1.

[0054] Example 3 The difference between this embodiment and Embodiment 1 is that: In S100: the slice layer thickness is set to 60μm.

[0055] In S200, the additive manufacturing process parameters are: laser power 500W, scanning speed 1500mm / s, scanning line spacing 0.14mm, slice layer thickness 60μm, and substrate preheating temperature 120℃.

[0056] In S300: the stress-relief annealing temperature is 850℃, and the holding time is 4h.

[0057] In S400: the solution treatment temperature is 960℃, and the holding time is 2h; the aging treatment temperature is 650℃, and the holding time is 5h; the heating rate is 10℃ / min.

[0058] In S500: the ultrasonic rolling frequency is 27.2kHz, the ultrasonic amplitude is 10μm, the static preload is 900N, the spindle speed is 450r / min, and the axial feed is 0.07mm / r; the pulsed laser wavelength is 1061nm, the laser shock pulse width is 20ns, the single pulse energy is 30J, the scanning overlap rate is 45%, and the number of shock passes is 3.

[0059] The remaining steps are the same as in Example 1.

[0060] Comparative Example 1 The difference between this comparative example and Example 1 is that solution treatment and aging treatment are not performed in step S400; only stress-relieving annealing treatment in step S300 is performed. The remaining steps are the same as in Example 1.

[0061] Comparative Example 2 The difference between this comparative example and Example 1 is that only laser shock peening is performed in step S500, and ultrasonic rolling peening is not performed. The remaining steps are the same as in Example 1.

[0062] Comparative Example 3 The difference between this comparative example and Example 1 is that in step S500, laser shock peening is performed first, followed by ultrasonic rolling peening (the order is reversed). The remaining steps are the same as in Example 1.

[0063] The performance of the TC4 titanium alloy impact brakes prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1.

[0064]

[0065] As can be seen from Table 1, the TC4 titanium alloy impact brakes prepared in Examples 1-3 all meet the requirements of high-impact service conditions for brakes. Compared with Example 1, the impact energy, tensile strength, yield strength, and elongation after fracture of the brake prepared in Comparative Example 1 decreased by 46.4%, 19.0%, 18.6%, and 33.3% respectively at -40℃. This is because Comparative Example 1 did not undergo solution aging heat treatment, indicating that solution aging heat treatment is not a simple post-processing step, but a key guarantee for the reliable service of the brake under high chamber pressure and high alternating impact conditions. Solution treatment retains the high-temperature structure to room temperature through water quenching, while aging treatment promotes the uniform precipitation of fine dispersed phases. The two work together to achieve the optimal match between strength and impact toughness.

[0066] As can be seen from Examples 1 and Comparative Examples 2-3, the combined strengthening of ultrasonic rolling and laser shock and their execution order have a decisive influence on the formation of the compressive stress layer. In Comparative Example 2, when only laser shock strengthening was performed without ultrasonic rolling, the depth of the residual compressive stress layer was only 0.6 mm. This is because the defects such as open pores and melt channel pits on the surface of the ankylothermal device obtained in Comparative Example 2 were not closed beforehand, resulting in the laser shock energy not being effectively transferred to the deep material. In Comparative Example 3, the strengthening process order of ultrasonic rolling and laser shock was changed, and the compressive stress layer depth of Comparative Example 3 was increased to 0.8 mm, but it was still much lower than the 1.4 mm of Example 1. This is because the micro-pits formed on the surface of the ankylothermal device by laser shock strengthening were partially flattened in the subsequent ultrasonic rolling, and the deep compressive stress was not fully preserved. In addition, the continuity of the compressive stress distribution was poor, and there were stress troughs. Therefore, it can be seen from Example 1 and Comparative Examples 2-3 that the specific order of ultrasonic rolling followed by laser impact plays an irreplaceable synergistic role. Ultrasonic rolling closes surface defects first and provides a flat surface, creating favorable conditions for the adhesion of the laser impact absorption layer, enabling the energy of the laser impact to be effectively transferred to the deep layer and form a continuous compressive stress layer.

[0067] Moreover, judging from the test results of Comparative Examples 1-3, the heat treatment strengthening, ultrasonic rolling strengthening, laser shock strengthening, and the combination order of the three in this invention are all indispensable technical means to achieve excellent comprehensive performance. There is a clear synergistic relationship between each step, and the technical features together constitute an organic whole technical solution, rather than a simple superposition of independent processes.

[0068] The foregoing has provided a detailed description of a TC4 titanium alloy impact brake and its additive manufacturing method. Specific examples have been used to illustrate the principles and implementation methods of this application; the descriptions of the embodiments are merely for the purpose of helping to understand the core ideas of this application. It should be noted that those skilled in the art can make various improvements and modifications to this application without departing from its principles, and these improvements and modifications also fall within the protection scope of the claims of this application.

Claims

1. An additive manufacturing method for a TC4 titanium alloy impact brake, characterized in that, The method includes the following steps: S100. Construct an integrated three-dimensional model of the TC4 titanium alloy impact brake to be manufactured, and add a support structure at the suspended position of the three-dimensional model. Then, slice the three-dimensional model to generate laser scanning paths for each layer. The laser scanning path adopts a scanning strategy of partition scanning combined with interlayer rotation. S200. According to the laser scanning path generated in step S100, under the protection of inert gas, the pre-selected TC4 titanium alloy powder is melted and deposited layer by layer by laser selective melting method to form a shrinkage device blank. S300: Separate the brake blank from the substrate and remove the support structure; S400. The blank of the brake after removing the support structure is subjected to heat treatment, wherein the heat treatment includes solution treatment and aging treatment performed sequentially. S500, The heat-treated blank of the brake is subjected to composite strengthening, wherein the composite strengthening includes ultrasonic rolling strengthening and laser shock strengthening performed sequentially. S600, the composite-strengthened muzzle brake blank is precision machined to obtain the finished TC4 titanium alloy impact muzzle brake.

2. The additive manufacturing method for the TC4 titanium alloy impact brake according to claim 1, characterized in that, In step S100, the partition scanning is an island-style partition scanning, and the interlayer rotation angle is 67°.

3. The additive manufacturing method for the TC4 titanium alloy impact brake according to claim 1, characterized in that, In step S100, the three-dimensional model has a machining allowance of 0.3-0.5mm, and the three-dimensional model is placed vertically on the substrate with the connecting end of the retractor facing downwards, and the axis of the retractor is perpendicular to the plane of the substrate; the support structure is a mesh support, and the mesh support has a peeling layer of 0.1-0.2mm on the contact surface with the three-dimensional model.

4. The additive manufacturing method for the TC4 titanium alloy impact brake according to claim 1, characterized in that, In step S200, the process parameters for laser selective melting are: laser power 300-500W, scanning speed 800-1500mm / s, scanning line spacing 0.08-0.14mm, slice layer thickness 30-60μm, and substrate preheating temperature 80-120℃.

5. The additive manufacturing method for the TC4 titanium alloy impact brake according to claim 1, characterized in that, Step S300 further includes: performing stress-relief annealing after removing the support structure, wherein the process parameters for stress-relief annealing are: vacuum degree ≤ 5 × 10⁻⁶. -3 Hold at 800-850℃ for 2-4 hours, then cool in the furnace to below 200℃ before unloading.

6. The additive manufacturing method for the TC4 titanium alloy impact brake according to claim 1, characterized in that, In step S400, the process parameters for solution treatment are: holding at 900-960℃ for 1-2 hours followed by water quenching, with a cooling rate ≥50℃ / s; the process parameters for aging treatment are: holding at 500-650℃ for 3-5 hours followed by furnace cooling.

7. The additive manufacturing method for the TC4 titanium alloy impact brake according to claim 1, characterized in that, In step S500, the process parameters for ultrasonic rolling strengthening are: frequency 27.2-28.8kHz, ultrasonic amplitude 7-10μm, static preload 700-900N, spindle speed 350-450r / min, axial feed 0.05-0.07mm / r, and single rolling pass.

8. The additive manufacturing method for the TC4 titanium alloy impact brake according to claim 7, characterized in that, In step S500, the process parameters for laser shock peening are: 1061-1067nm pulsed laser, pulse width 15-20ns, single pulse energy 22-30J, square spot size 4mm×4mm, scanning overlap rate 35%-45%, and number of shock passes 2-3 times. In this process, 0.10mm high-purity aluminum foil is used as the absorption layer, and 1.0-1.5mm thick continuously flowing deionized water film is used as the constraint layer.

9. The additive manufacturing method for the TC4 titanium alloy impact brake according to claim 1, characterized in that, It also includes S400', which involves pre-treating the heat-treated shrinkage device blank before composite strengthening. Specifically, the pre-treatment involves grinding the heat-treated shrinkage device blank to Ra≤3.2μm, followed by acetone soaking, anhydrous ethanol ultrasonic cleaning, and drying.

10. A TC4 titanium alloy impact brake, characterized in that, The TC4 titanium alloy impact brake, prepared by the method according to any one of claims 1 to 9, has the following material properties: impact energy at -40℃ ≥ 25 J / cm². 2 Tensile strength ≥1000MPa, yield strength ≥840MPa, elongation after fracture ≥14%.

Citation Information

Patent Citations

  • Method for improving fracture toughness of additive manufacturing TC4 titanium alloy material

    CN112962041A

  • Method for strengthening spraying hole wall of titanium alloy muzzle brake

    CN114000142A

  • A method of manufacturing a titanium alloy barrel brake with a ta-w coating

    CN117512589B